Exploring knowledge management implementation: a case of International Islamic University Malaysia - Zakaria, Maznah (Library Association of Singapore (LAS), 2024)
This paper presents the implementation of knowledge management (KM) at the International Islamic University Malaysia (IIUM). The author begins with an exploration of knowledge and KM concepts. Factors influencing the implementation of KM at IIUM are also discussed and a conducted knowledge audit as well as subsequent analysis are presented, culminating in actionable recommendations. The recommendations aim to enhance IIUM’s KM initiatives, suggesting approaches for successful implementations. By addressing key areas identified in the audit, IIUM can consider ways to develop a more effective and successful KM journey by optimising their developed KM practices, and foster a culture of knowledge sharing and utilisation.